A integração comercial entre China e asiáticos e os ganhos competitivos em terceiros mercados - Linck, Priscila (Universidade do Vale do Rio dos Sinos, 2021)
Since China's accession to the WTO (World Trade Organization) in 2001, the country has significantly expanded its participation in world trade, becoming the world's largest exporter in 2009. This movement brought a series of concerns and questions about the competitiveness of countries in international trade, mainly Asian, in view of the dependence of their economies on exports. At the same time, it is argued that the commercial integration of Asian countries with China, along with the expansion of the market, may have generated an increase in the competitiveness of Asian countries in international trade, due to efficiency gains and economies of scale. The empirical study presented in this dissertation aimed to measure the effect of the competitiveness of Chinese exports on the competitiveness of exports from the countries of East Asia and Southeast Asia, likewise India, considering the intra-industrial trade of the respective countries with China, in the period from 2000 to 2019. In other words, we tried to test the hypothesis that the Asian countries' trade integration with China prevents them from losing international competitiveness due to the increase in Chinese competitiveness in international trade. In order to achieve this goal, panel data models were estimated using the estimator of Blundell de Bond (1998), GMM-SYS, for industrial products segmented into four sectoral taxonomies of Pavitt (1984), the variable of interest being an interaction between China's market-share in third markets and the China Intra-Industry Trade Index with Asian countries. The results confirm the hypothesis that the intra-industry trade of Asian countries with China increases the market-share of Asian exports in international trade, together with an increase in the Chinese exports market-share. In addition, the size of competitive gains varies between industrial sectors, being greater in sectors that arescale intensive.
Keywords: China; Comércio intraindústria; Competitividade; Métodos generalizados dos momentos; Intra-industry trade; Competitiveness; Generalized methods of moments; ACCNPQ::Ciências Sociais Aplicadas::Economia